Cocaine‐associated atypical haemolytic uraemic syndrome in a genetically susceptible individual. Issue 7 (17th January 2020) - Bongetti, Elisa; Kavanagh, David; Martin, Kylie; Bendall, Anna; Hill, Prue; Steinberg, Adam; Rajaram, Yogeshwar; Ierino, Francesco
Abstract: Atypical haemolytic uraemic syndrome (aHUS) is a severe, life‐threatening condition that requires early recognition and urgent treatment. In aHUS rare genetic variants in CFH, CFI, CD46, C3 and CFB predispose to complement over activation. This case describes a case of aHUS in which there was a strong temporal association between disease onset and the use of smoked cocaine. The patient was found to have a rare genetic variant in the CFI gene which may have been unmasked by first‐time exposure to cocaine. The patient stabilized and improved with early administration of eculizumab, supporting the notion of an underlying immunological pathogenesis and the importance of early intervention. SUMMARY AT A GLANCE: Atypical haemolytic uraemic syndrome requires a complex and comprehensive diagnostic approach and specific therapeutic management which has been well described in the index patient who harbours a rare genetic variant in the CFI gene which may have been unmasked by exposure to cocaine.